2004
DOI: 10.1002/chin.200431007
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Signature of Structures Associated with the H+(H2O)n (n = 6 to 27) Clusters.

Abstract: 27) Clusters. -Size-selected protonated water clusters H + (H 2 O) n (n = 6-27) are characterized by IR spectroscopy of OH stretches in the gas phase. Spectral features disappearing for the n = 21 magic cluster indicate that all the dangling OH groups arise from water molecules in similar binding sites. It is suggested that the n = 21 cluster structure consists of a dodecahedral cage with a single interior water molecule. -(SHIN, J.-W.; HAMMER, N. I.; DIKEN, E. G.; JOHNSON*, M. A.; WALTERS, R. S.; JAEGER, T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
228
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(240 citation statements)
references
References 1 publication
12
228
0
Order By: Relevance
“…In this paper, we contrast the behavior of the n = 20 hydrates of the H 3 O + and Cs + ions, both of which are preferentially generated in the M + (H 2 O) n cluster ion distributions (i.e., are magic numbers) and are thought to be based on a pentagonal dodecahedron motif (12 interconnected H-bonded pentagons). An important difference between these ions is that H 3 O + is predicted to reside on the surface of the cage (6,8,26), whereas Cs + is sequestered in its interior (27,28). We follow the evolution of the bands in the perdeuterated isotopologues, Cs + (D 2 O) 20 and D 3 O + (D 2 O) 20 , and find strong support for the earlier assignment of the spectral signature of the embedded H 3 O + ion.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…In this paper, we contrast the behavior of the n = 20 hydrates of the H 3 O + and Cs + ions, both of which are preferentially generated in the M + (H 2 O) n cluster ion distributions (i.e., are magic numbers) and are thought to be based on a pentagonal dodecahedron motif (12 interconnected H-bonded pentagons). An important difference between these ions is that H 3 O + is predicted to reside on the surface of the cage (6,8,26), whereas Cs + is sequestered in its interior (27,28). We follow the evolution of the bands in the perdeuterated isotopologues, Cs + (D 2 O) 20 and D 3 O + (D 2 O) 20 , and find strong support for the earlier assignment of the spectral signature of the embedded H 3 O + ion.…”
mentioning
confidence: 54%
“…The intramolecular HOH bending and OH stretching modes of the surface water molecules are not strongly shifted by introduction of the ion, however, where the latter appear as a broad envelope spanning the 3,000-to 3,700-cm −1 range typical of liquid water. An interesting aspect of the D 2 tagged spectrum obtained with cryogenic cooling (as opposed to that reported on the same ion generated under the more rapid quenching conditions at play in a supersonic jet ion source) (8,11) is that distinct features begin to emerge above the continuous background absorption in the OH stretching region above 3,400 cm −1 .…”
mentioning
confidence: 87%
“…Experimentally, the IR spectra are being used to identify the geometrical structure of small clusters. [10,11,13,22,23] At the same time, theoretical IR spectra of water clusters are frequently simulated based on quantum-chemical computations to help determine the molecular structure of water clusters through comparing with experimental results. [5,6,[24][25][26] Regarding quantum-chemical studies of vibrations of larger clusters, the IR spectra of different (H 2 O) 20 isomers were calculated by Fanourgakis et al at the level of MP2 theory, where they demonstrated the different spectral features for the isomers and that these features could be related to the spectra of their constituent fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of water clusters have shed light not only on their fundamental properties (1)(2)(3)(4) but also on the mechanism employed by various nano-bio systems to fine-tune water and proton transport (5)(6)(7)(8)(9). A relevant example from biology is the M2 protein of the influenza A virus (10,11), which is the target of the influenza drugs amantadine and rimantadine (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%